2005
DOI: 10.1161/01.cir.0000152102.29293.d7
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Depressive Symptoms Have Lower Health Status Benefits After Coronary Artery Bypass Surgery

Abstract: Background-Depression is an established independent prognostic factor for mortality, readmission, and cardiac events after CABG surgery. However, limited data exist on whether depression influences functional outcomes after CABG. Methods and Results-We followed 963 patients who underwent first CABG between February 1999 and February 2001. At baseline and at 6 months after CABG, we interviewed patients to assess depressive symptoms using the Geriatric Depression Scale (GDS) and physical function using the Sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
160
3
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(183 citation statements)
references
References 52 publications
11
160
3
9
Order By: Relevance
“…The latter is important because ~25% of CVD events are associated with PSS, which has been independently shown to be associated with prolonged hospitalization, delayed return to work, and heightened mortality. 99,100 The effects of PSS appear to be cumulative, and are inversely related to HRQoL. 101 In studies that have evaluated major dimensions of HRQoL on post-MI and post-CABG patients using disease-specific and general outcome measures, CR has been reported to enhance PSS profiles, and HRQoL scores.…”
Section: Health-related Quality Of Life and Psychosocial Stress In Camentioning
confidence: 99%
“…The latter is important because ~25% of CVD events are associated with PSS, which has been independently shown to be associated with prolonged hospitalization, delayed return to work, and heightened mortality. 99,100 The effects of PSS appear to be cumulative, and are inversely related to HRQoL. 101 In studies that have evaluated major dimensions of HRQoL on post-MI and post-CABG patients using disease-specific and general outcome measures, CR has been reported to enhance PSS profiles, and HRQoL scores.…”
Section: Health-related Quality Of Life and Psychosocial Stress In Camentioning
confidence: 99%
“…In this issue of Circulation, Mallik et al 4 add to our understanding of the relationship between depression and outcome in cardiac patients. Prospectively evaluating 963 coronary artery bypass graft (CABG) surgery patients, they found that 25% had substantial perioperative depressive symptoms.…”
Section: See P 271mentioning
confidence: 99%
“…[14][15][16][17] Arrhythmia occurs frequently in patients with depression, irrespective of the presence of coronary artery disease. [18][19][20][21][22][23] One of the plausible mechanisms explaining the relationship between depression and arrhythmia is autonomic dysfunction. Patients with depression have altered secretion of norepinephrine, a higher resting heart rate, low heart rate variability, and reduced baroreflex sensitivity, [23][24][25][26][27][28][29] resulting in resting sinus tachycardia.…”
Section: Résumémentioning
confidence: 99%